Health and Economic Outcomes in the Alumni of the Wounded Warrior Project - Krull, Heather (RAND Corporation, 2012)
The Wounded Warrior Project (WWP) provides those injured during service on or after September 11, 2001, access to programs that ensure that wounded warriors are well-adjusted in mind, spirit, and body and that they are economically empowered. Here the authors report a detailed analysis of how alumni were meeting these goals and how their outcomes compared with the outcomes of other veteran and nonveteran U.S. populations.